ChemInform Abstract: Trivalent Cation‐Controlled Phase Space of New U(IV) Fluorides, Na3MU6F30 (M: Al3+, Ga3+, Ti3+, V3+, Cr3+, Fe3+): Mild Hydrothermal Synthesis Including an in situ Reduction Step, Structures, Optical, and Magnetic Properties. Issue 17 (April 2015) - Yeon, Jeongho; Smith, Mark D.; Morrison, Gregory; zur Loye, Hans‐Conrad
Abstract Single crystals of the title compounds are hydrothermally synthesized in nearly quantitative yields from aqueous mixtures of UO2(OAc)2, NaF, HF, and Ti2O3, or V2O5, GaF3, or FeF2 for Na3MU6F30 (M: Ti, V, Ga, Fe), and from aqueous mixtures of NaUF5, HF, and Na3AlF6, or CrF3 for Na3MU6F30 (M: Al, Cr) (autoclave, 200 °C, 1 d).